Penegakan Hukum Terhadap Tindak Pidana Penyelundupan Penyu sebagai Satwa Terlindungi di Bali - I Komang Arya Sentana Mahendra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
Prohibition of all exploitation of protected animals. Even in the territory of Indonesia, turtle smuggling still occurs, especially in Bali Province where turtle smuggling often occurs. The purpouses of this research are to analyze the legal protection of turtles as protected animals and the criminal sanctions against the perpetrators of turtle smuggling as protected animals? The research method used is normative law, with statutory apporoach and conceptual approach. The results of the research show that forms of legal protection against turtles, if from the international agreement with the CITES agreement (Convention on International Trade in Endangered Species), in Indonesia there are 6 out of 7 types of turtles in the world that are protected under the turtle species law. existing in the protected world based on the law on the determination of wild protected animals, and the forms of sanctions against people who smuggle turtles as protected animals are in the form of administrative sanctions, civil sanctions and criminal sanctions. There are no specific criminal sanctions against turtle smugglers, these sanctions are still incorporated in Law No. 5 of 1990, concluded that legal protection and sanctions against turtles as protected animals in the form of administrative, civil and criminal sanctions, specifically in Bali there are no criminal sanctions against turtle smugglers.